Banking Sector Intermediation Development and Economic Growth: Evidence from Nigeria. Issue 3 (3rd July 2022) - Bernard Azolibe, Chukwuebuka
ABSTRACT: In developing economies, banks act as a conduit for the efficient mobilization of financial resources from the surplus sectors for effective allocation to the deficit sectors for productive investment that will in turn lead to economic growth. Thus, the study is aimed at evaluating whether development in the banking sector intermediation process in the form of an increase in the number of branches, credit to private sectors, intermediation efficiency and total assets stimulated economic growth in Nigeria during the period 1987⎯2018. The study employed the Johansen cointegration test, dynamic ordinary least square regression and error correction model in determining the relationship between the variables. The results of the cointegration test confirmed the existence of a long-run relationship between banking sector development indicators and economic growth in Nigeria; whereas in the short-run only number of bank branches and bank's total assets have a positive and significant impact on economic growth, signifying that much of Nigeria's superior growth performance is attributed to an increase in the number of bank branches and growth in the bank's total assets. Going by the above findings, the study recommends that the Central Bank of Nigeria should monitor the activities of Commercial Banks in terms of branch distribution to ensure a wider spread and even distribution and also review the asset base of banks from time to time so as to measure up to international standards in order to increase investment and economic growth.